Peran Masjid Sabilil Huda Boki Owutango dalam Pemberdayaan Ekonomi Syariah di Tamalate - Mohamad Akbar F. Ibrahim; Sri Dewi Yusuf; Yusran Zainuddin (Jurnal Ekonomi Islam, 2024)
This research highlights the role of Masjid Sabilil Huda Boki Owutango in Tamalate in empowering the sharia economy through various programs such as entrepreneurship training, business capital assistance, management of zakat, infaq, and sedekah, as well as community savings. Using a qualitative approach, this study shows that the mosque has successfully enhanced understanding and application of sharia economic principles, created new job opportunities, reduced economic disparities, and improved the fair distribution of wealth. The active participation of the congregation in these programs demonstrates the effectiveness of the mosque's efforts in empowering the community, making it a significant center for social and economic activities in improving the welfare of the Tamalate community.